The Role of School Libraries in Promoting Reading Interest Among Elementary School Students in Purwakarta: A Descriptive Study - Gina Permata Sari; Wahyu Sopandi (Jurnal Elementaria Edukasia, 2026)
The strengthening of reading interest in elementary school students cannot rely solely on encouragement to read, but requires an enabling literacy ecosystem that is close to children’s daily learning experiences. The school library is expected to function as a learning resource center and a literacy space, yet its role is often uneven due to collection quality, facilities, and management. This study aims to describe the role of the school library in fostering sixth-grade students’ reading interest in a private Islamic elementary school in Purwakarta. The research employed a qualitative approach with a descriptive design. Data were collected through student questionnaires, observations of library use, and interviews with teachers and librarians, involving 76 students, 22 teachers, and 2 librarians. Data analysis used an interactive model supported by method and source triangulation. The findings indicate that students’ reading interest tends to be positive and aligns with the library’s functioning, reflected in weekly visits (70%), interest in reading beyond textbooks (72%), positive perceptions of collection attractiveness (80%) and room comfort (75%), as well as the library’s perceived support for learning activities (63%). Digital use has begun to emerge (65% using computers/e-books), but digital library integration remains inconsistent among teachers (70% not routine). Key constraints include limited child-friendly fiction collections and uneven home–school collaboration to sustain reading habits outside school. It can be concluded that the school library plays a multidimensional role in supporting reading interest; however, strengthening relevant collections, hybrid literacy services (print, digital), and sustained school parent collaboration is essential for long-term impact. Keywords: chool library, reading interest, elementary students